Weather forecast for the 35th America's Cup (2017) winners based on a limited area model. (3rd February 2020) - Messager, Christophe; Badham, Roger "Cloud"; Honnorat, Marc; Vandenberghe, François; Waterhouse, Tom; Currie, Ian
Abstract: The America's Cup (AC) is the oldest trophy in international sport and sailing regatta. The 35th AC occurred during spring 2017 in Bermuda. A new generation of sailing boats was in use, while the technical advances required backstage to enable a victory were equally impressive. The availability of accurate wind fields with a grid spacing of < 1 km from numerical meteorological forecasts was one of those key advances, used for both strategic and tactical planning. The study describes the limited area model, explicitly resolving the convection, used to generate weather forecasts for Emirates Team New Zealand (ETNZ) challenger, the challenger and winning team. In particular, it illustrates an ability to forecast accurately the wind variability in space and time, which helped achieve victory. Abstract : Map of the Bermuda main islands: (a) location of the Bermuda Islands within the Northern Atlantic; (b) location of the Crescent Reef meteorological station; (c location of the) airport meteorological station; (d) cumulus cloud above the main island as displayed on the (unavailable) AC2017 official website; (e) races site in the Great Sound; and (f) location of the Pearl Island meteorological station.